Pengaruh Teknologi Informasi, Kompensasi, dan ... (Christoporus TPN & Mulyanto) 55 PENGARUH TEKNOLOGI INFORMASI, KOMPENSASI, DAN MOTIVASI TERHADAP KINERJA PEGAWAI DINAS PENDAPATAN, PENGELOLAAN KEUANGAN DAN ASET DAERAH KABUPATEN KLATEN DENGAN KEPUASAN KERJ - Christoporus Tri Prasetyo Nugroho & Mulyanto (Universitas Slamet Riyadi, 2014)
This study aimed is to determine the effect of information technology, compensation and motivation on employee performance Department of Revenue Service, Finance and Asset Management Klaten Regency with job satisfaction as an intervening variable. This study took a sample of 56 respondents, employees of DPPKAD Klaten regency, with a random sampling technique. The data in this research will be obtained directly from the questionnaires. The data analysis using path analysis, t-test, F-test and R Total. Regression equation results showed that information technology is not a significant influence on job satisfaction of employees. Compensation is not a significant influence on job satisfaction of employees. Motivation has significant effect on employee job satisfaction. Information technology has a significant effect on employee performance. Compensation has a significant effect on employee performance. Motivation has a significant effect on employee performance. Employee satisfactions significantly influence employee performance. The conclusion of this line of analysis suggests that the use of intervening variables of employee job satisfaction in order to improve performance, for variable information technology and compensation is not effective, where as motivation variable is effective. Keywords: information technology, compensation, motivation, employee performance, job satisfaction.